Flexible Peak Shaving Technology for Coal-Fired Boilers Based on Intelligent Control - Minhang SONG; Hongyan YANG (南方能源建设)
[Introduction] With the increasing demand for flexible peak shaving of thermal power units and the rapid development of information technology, thermal power enterprises are shifting from the traditional operation and management mode toward a cleaner, more efficient, reliable digital and intelligent mode. How to improve the intelligence, precision and reliability of coal-fired units in the flexible peak-shaving process has become a key issue of concern to those in the industry. [Method] Aiming at the deep peak shaving demand of the power system, this paper summarized the typical problems in the process of flexible peak shaving and analyzed the overall development of control theory applied to boilers in coal-fired units. Based on this, this paper conducted a comprehensive analysis of coal-fired boiler flexible peak shaving algorithm models and their applications based on intelligent control from four aspects: optimization control of boiler combustion performance, precise control of wide-load denitration, boiler operational energy efficiency control, and monitoring and diagnosis of main and auxiliary machinery equipment. [Result] On this basis, the research progress and application effects of intelligent control theory and models in the flexible peak shaving of coal-fired boilers are discussed in detail. [Conclusion] At present, based on the common problems in the flexible peak-shaving process of coal-fired boilers, it is necessary to improve the accuracy of basic data acquisition, promote the complementary integration of data and knowledge, and strengthen multi-objective optimization control and DCS control system optimization on the basis of the stable combustion ability improvement of the combustion organization method. At the same time, it is important to consider the dialectical optimization relationship between peak shaving economy and unit life, thereby providing intelligent and precise solutions to improve the flexible peak shaving capabilities of coal-fired boilers.